2013
DOI: 10.1111/cei.12183
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral blood compartment in patients with Graves' disease: activated T lymphocytes and increased transitional and pre-naive mature B lymphocytes

Abstract: SummaryGraves' disease (GD) is an autoimmune disease that involves aberrant B and T lymphocyte responses. Detailed knowledge about lymphocyte subpopulation composition will therefore enhance our understanding of the pathogenesis of GD and might support the development of new immunomodulatory treatment approaches. The aim of this study was to gain detailed insight into the composition of the peripheral blood lymphocyte compartment in GD before and during anti-thyroid drug therapy. Major B and T lymphocyte subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Recently, van der Weerd et al described a trend towards increased numbers of naive T-lymphocytes and RTE in patients with GD receiving antithyroid drug therapy. 18 Consistent with this in our cohort, delta C t was lower among those treated with thyreostatic medication than those treated with radioiodine/ surgery. Whereas this weak effect (P = 0Á6) cannot explain pronounced differences between GD and controls found by us, it is intriguing and deserves further studies.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, van der Weerd et al described a trend towards increased numbers of naive T-lymphocytes and RTE in patients with GD receiving antithyroid drug therapy. 18 Consistent with this in our cohort, delta C t was lower among those treated with thyreostatic medication than those treated with radioiodine/ surgery. Whereas this weak effect (P = 0Á6) cannot explain pronounced differences between GD and controls found by us, it is intriguing and deserves further studies.…”
Section: Discussionsupporting
confidence: 89%
“…When we compared the group1 and 2, leukocyte and neutrophil counts were similar, and lymphocyte counts were signifi cantly higher in Graves' patients compared to the control group. Van der Weerd K and et al reported that with fl ow cytometry method analysis, T and B lymphocyte counts were signifi cantly higher in Graves' disease than in healthy control group and in the same study there was a positive correlation between the levels of ft4 and B lymphocytes (14). Although antithyroid drugs are known to cause neutropenia as a side effect (15), Peng Y and et al, reported that compared with untreated Graves' patients, neutrophil counts increase in Graves patients who are euthyroid with treatment (16).…”
Section: Discussionmentioning
confidence: 70%
“…CD5 lymphocytes are considered the principal cells that produce autoantibodies against IgM. They can form an authoritative cell bank that is linked to the development of autoimmune diseases [31][32][33]. Our results revealed that CD19+CD5+, CD19+CD80+, and CD19+CD86+ B cell abundances were significantly higher in patients with anti-EBVCA IgM positivity than in patients with anti-EBVCA IgM negativity.…”
mentioning
confidence: 67%